Efeito protetor da amifostina e da via sulfeto de hidrogênio / canais de potássio ATP - dependentes na cistite hemorrágica experimental - Batista, Cristina Kelma Loiola Ponte (2016)
Hemorrhagic cystitis (HC) is an important side effect of acrolein (ACR), a metabolite of the anticancer agents oxazaphosphorines. Amifostine (AMF) is a cytoprotective agent, which protects normal tissues from anticancer chemotherapy-associated toxic effects. Recent studies reported the involvement of hydrogen sulfide (H2S) in various physiological and pathological conditions, as well as the constitutive production in mammalian tissues. This study aimed to investigate the protective effect of Amifostine and H2S in IFO-induced HC in mice. Swiss male mice were injected with either ACR (75 mcg, ive) or IFO (400 mg/kg, ip), and were killed 3 or 12 hours, respectively. Another group of animals received Amifostine (AMF, 50mg/kg) 30 minutes before the ACR or IFO. Cell apoptosis, in vivo and in vitro bladder motor function, expression of pro-inflammatory cytokines and enzymes were measured. To investigate the protective effect of H2S, the mice were treated with L-cysteine (25. 50 or 100 mg/kg, po) or Lawesson's reagent (9, 27 or 81 mmol/kg, po) or glibenclamide (10 mg/kg, po) + L-cysteine (50 mg/kg, po). The in silico analysis showed the likely chemical interaction between AMF and acrolein. In in vivo studies, ifosfamide induced significant (P<0.05) increase in bladder wet weight, gross and histopathological changes, immunostaining of TNF-alpha, IL-1beta and iNOS and COX-2, as well as increased apoptotic index and bladder dysfunction. Interestingly, AMF pretreatment significantly prevented all these changes (P<0.05 versus ifosfamide), suggesting its potential uroprotective effect. In another experimental approach, the uroprotective activity of H2S was showed by the reduction of bladder wet weight, vascular permeability, macroscopic and microscopic injury, myeloperoxidase activity as well as in vitro bladder dysfunction (P<0.05 vs IFO). Such protection was reversed by pretreatment of animals with glybenclamide (P<0.05 vs L-cysteine + IFO). Therefore, the present study showed the protective effect of amifostine on IFO-induced HC, probably by a chelate effect on acrolein and the modulation of vascular and inflammatory events. Additionally, hydrogen sulfide also demonstrated uroprotective effect by an ATP-dependent potassium channel dependent manner.